Akses Informasi Pemustaka Tunanetra Pada Layanan Braille Corner Di Dinas Kearsipan Dan Perpustakaan Kota Jambi - Putri, Oktaviani Dwi; Rum, Muhammad (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2021)
Introduction. This research is entitled Information Seeker Behavior of Blind Users in Braille Corner Services at the Jambi City Archives and Libraries Service, the purpose of this study is to determine the behavior of the blind in seeking information at the Jambi City Archives and Library Service. Information seeking behavior arises because of the need for information, so the higher the need for information, the higher the number of activities seeking information. Information behavior by users has its own pattern. Because each user will find the information they need differently, therefore the need for information is very important. From this difference, the writer is interested in studying